The Role of Digital Leadership, e-loyalty , e-service Quality and e-satisfaction of Indonesian E-commerce Online Shop - Purwanto, Agus (International Journal of Social and Management Studies, 2022)
Abstract - The purpose of this study was to determine the effect of e-service quality on e-loyalty, digital leadership on e-loyalty, the effect of e-service quality on e-satisfaction and the effect of e-loyalty on e-satisfaction in e-commerce online shops. The research method is quantitative and the sampling of respondents uses non-probability sampling of 190 online shop consumers. The researchiuses quantitativeimethods with descriptiveianalysis techniquesiand pathianalysis. The resultsiof theionline questionnaireiwere measurediusing a Likertiscale. Data processingiis doneibyipathianalysisimethodiusingiSPSS . The results of his research prove that the variables of digital leadership, e-service quality, e-satisfaction and e-loyalty are in the good category. The results of his research prove that digital leadership has aipositive andisignificantieffect on e-loyalty, digitalileadership has aipositive andisignificantieffect on e-satisfaction , e-serviceiquality has a positiveiand significant effect on e-loyalty, e-service quality has a positive and significant effect on e-satisfactioniand e-loyaltyihas aipositive and significantieffect on e-satisfaction in e-commerce online shops.